Substrate effects on the speed limiting factor of WSe2 photodetectors. Issue 41 (14th October 2022) - Schedel, Christine; Strauß, Fabian; Kohlschreiber, Pia; Geladari, Olympia; Meixner, Alfred J.; Scheele, Marcus
Abstract : The speed of a WSe2 photodetector can be affected by the chosen substrate material, apparent as the detector on polyimide is independent of the applied electric field, while the one on glass can be accelerated up to a 3 dB bandwidth of 2.6 MHz. Abstract : We investigate the time-resolved photoelectric response of WSe2 crystals on glass and flexible polyimide substrates to determine the effect of a changed dielectric environment on the speed of the photodetectors. We show that varying the substrate material can alter the speed-limiting mechanism: while the detectors on polyimide are RC limited, those on glass are limited by slower excitonic diffusion processes. We attribute this to a shortening of the depletion layer at the metal electrode/WSe2 interface caused by the higher dielectric screening of glass compared to polyimide. The photodetectors on glass show a tunable bandwidth, which can be increased to 2.6 MHz with increasing the electric field.